2016
DOI: 10.1007/978-94-024-0942-0_13
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Hepatitis E Vaccine

Abstract: Hepatitis E has been increasingly recognized as an underestimated global disease burden in recent years. Subpopulations with more serious infection-associated damage or death include pregnant women, patients with basic liver diseases, and elderly persons. Vaccine would be the most effective means for prevention of HEV infection. The lack of an efficient cell culture system for HEV makes the development of classic inactive or attenuated vaccine infeasible. Hence, the recombinant vaccine approaches are explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 90 publications
0
15
0
1
Order By: Relevance
“…It is debated whether these strains reflect the behavior of wild-type HEV [26]. The lack of a reproducible cell culture system susceptible to wild-type HEV also hampers the approach to generate a classic inactive or attenuated vaccine [27], to develop and test specific drugs or to identify strategies for efficient HEV inactivation [28].…”
Section: Introductionmentioning
confidence: 99%
“…It is debated whether these strains reflect the behavior of wild-type HEV [26]. The lack of a reproducible cell culture system susceptible to wild-type HEV also hampers the approach to generate a classic inactive or attenuated vaccine [27], to develop and test specific drugs or to identify strategies for efficient HEV inactivation [28].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the results showed that shortening the period of infection can lower the incidence of HEV, representing another effective intervention and suggesting that we should aim for early detection, early diagnosis, and early treatment for controlling HEV transmission. To achieve this, it is necessary to improve the detection rate and treatment of hepatitis E. In addition, a study has shown that the hepatitis E vaccine has a good effect on controlling the disease [ 29 ], and our study also showed that the higher the vaccination coefficient, the more the incidence rate decreases. When the vaccination coefficient was 60%, the incidence has already decreased even more significantly.…”
Section: Discussionmentioning
confidence: 56%
“…An individual’s HEV IgG “antibody maintenance time” after infection with HEV exceeds 14 years [ 29 ]; thus, f = 1/(14 × 12) = 0.00595. Based on the literature, the survival time of HEV in water and the environment is 1/ ε , about 3 weeks; thus, thus we set ε = 1.3333 [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although a prophylactic vaccine for HEV has been developed, it is only licensed in China, this vaccine is effective against HEV genotypes 1 and 4. [27] Chronic HEV infection Figure 1. Treatment algorithm for the chronic HEV infection for transplant recipients.…”
Section: Prevention From Hev Infectionmentioning
confidence: 99%